Composite solid electrolyte, preparation method thereof and lithium solid-state battery

By adsorbing fast ion conductor ceramic particles and Ding Erxia on PVDF fiber support membrane, and dried lithium salt solution to form a composite solid electrolyte, solve the problem of poor existing electrolyte thickness and poor guidance ion ability, and achieve higher conductive conductivity. Ability and mechanical strength.

CN119361845APending Publication Date: 2025-01-24SHENZHEN BAK POWER BATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411762956.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing organic and inorganic composite solid electrolytes have problems such as excessive electrolyte thickness and poor ion conduction ability.

Method used

The PVDF fiber support membrane is used as the support structure to adsorb the fast -ion conductor ceramic particles and Ding Ergi, and absorb the lithium salt solution to dry and dry to form a composite solid electrolyte.

Benefits of technology

It significantly enhances the mechanical strength of the solid electrolyte film, and improves its conductivity and reduces the thickness of the electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361845A_ABST
    Figure CN119361845A_ABST
Patent Text Reader

Abstract

The invention provides a composite solid-state electrolyte, a preparation method thereof and a lithium solid-state battery, and relates to the field of solid-state electrolytes. The preparation method of the composite solid electrolyte comprises the following steps: loading fast ion conductor ceramic particles on a PVDF fiber support membrane to form a first intermediate; absorbing butanedinitrile onto the first intermediate to form a second intermediate; and adsorbing a lithium salt solution onto the second intermediate, and drying to obtain the composite solid electrolyte. The PVDF fiber supporting film is used as a supporting structure, so that the mechanical strength of the solid electrolyte film can be enhanced, and the PVDF fiber supporting film can also be used as a conductive ion network to help lithium ion transportation. The PVDF fiber support membrane is coated with succinonitrile as a conductive ionic agent, the compounded membrane absorbs a lithium salt solution, and a PVDF-succinonitrile-lithium salt ternary eutectic system is formed in the drying process. The composite solid electrolyte prepared by the method disclosed by the invention has relatively small thickness and relatively excellent ion conduction capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of solid electrolytes, and in particular to a composite solid electrolyte and a preparation method thereof, and a lithium solid-state battery. Background Art

[0002] With the popularity of new energy vehicles, lithium-ion batteries, as the power source of new energy vehicles, have attracted much attention due to their portability, high energy density, high safety and many other advantages. However, traditional lithium-ion batteries are difficult to meet people's needs in terms of safety and energy density.

[0003] In recent years, researchers have focused more and more on solid-state batteries. Compared with traditional liquid lithium batteries, solid-state batteries have very obvious advantages. Solid-state batteries use solid electrolytes instead of liquid organic solvent electrolytes, and there is no risk of leakage or fire. In addition, due to the high oxidation potential of solid electrolytes, they can be used with high-nickel materials as the positive electrode of the battery, while the negative electrode can be matched with lithium metal, which has a much higher specific capacity than graphite, greatly improving the energy density. At the same time, since the manufacturing processes such as liquid injection of liquid batteries are omitted, the manufacturing steps can be simplified. Based on the above advantages, solid-state batteries are considered to be the best choice for the next generation of lithium batteries to replace traditional liquid lithium-ion batteries.

[0004] The core component of solid-state batteries is the solid electrolyte. Among them, the organic-inorganic composite solid electrolyte combines the advantages of ceramic oxide solid electrolytes and polymer solid electrolytes, taking into account ionic conductivity while having good interface contact. However, the existing organic-inorganic composite solid electrolytes have the problems of excessive electrolyte thickness and poor ion conductivity. Therefore, it is necessary to improve the organic-inorganic composite solid electrolyte. Summary of the invention

[0005] The purpose of this application is to provide a composite solid electrolyte and a preparation method thereof and a lithium solid-state battery to solve the above problems.

[0006] To achieve the above objectives, this application adopts the following technical solutions:

[0007] A method for preparing a composite solid electrolyte, comprising:

[0008] Adsorbing fast ion conductor ceramic particles on the PVDF fiber support membrane to form a first intermediate;

[0009] adsorbing succinonitrile onto the first intermediate to form a second intermediate;

[0010] The lithium salt solution is adsorbed onto the second intermediate and dried to obtain a composite solid electrolyte.

[0011] According to an embodiment of the present application, the fast ion conductor ceramic includes at least one of LLZTO, LLZO, LLTO, and LATP;

[0012] And / or, the lithium salt includes at least one of LiPF6, LiFSI, and LiTFSI.

[0013] According to an embodiment of the present application, the thickness of the PVDF fiber support membrane is 10 to 40 μm;

[0014] And / or, the porosity of the PVDF fiber support membrane is 60% to 80%;

[0015] And / or, the mass ratio of the fast ion conductor ceramic to the mass ratio of the PVDF fiber support membrane is 1:5 to 1:8;

[0016] and / or, the content ratio of the succinonitrile to the PVDF fiber support membrane is 1: (1400-1600) ml / mg;

[0017] And / or, the lithium salt solution comprises a lithium salt and an amide solvent;

[0018] And / or, the concentration of the lithium salt solution is 5 to 10 g / L;

[0019] and / or, the mass ratio of the lithium salt solution to the PVDF fiber support membrane is 7: (280-320) ml / mg;

[0020] And / or, the drying temperature is 50° C. to 60° C., and the drying time is 12 to 15 hours.

[0021] According to an embodiment of the present application, the forming of the first intermediate comprises: dropping a fast ion conductor ceramic suspension onto the PVDF fiber support membrane, and drying to remove the solvent in the fast ion conductor ceramic suspension to obtain the first intermediate;

[0022] The fast ion conductor ceramic suspension comprises fast ion conductor ceramic and alcohol solvent, and the content ratio of the fast ion conductor ceramic to the alcohol solvent is (1-2.5): 1 mg / ml;

[0023] and / or, the alcohol solvent comprises ethanol;

[0024] And / or, the amide solvent includes DMF.

[0025] According to an embodiment of the present application, the forming of the first intermediate includes: uniformly dripping a fast ion conductor ceramic suspension onto the PVDF fiber support membrane, followed by drying, turning over, and repeating the operations of dripping the fast ion conductor ceramic suspension, drying, and turning over until the fast ion conductor suspension is completely dripped.

[0026] According to an embodiment of the present application, the forming of the second intermediate comprises: heating succinonitrile at a temperature greater than or equal to the melting point of succinonitrile to obtain liquid succinonitrile, dripping the liquid succinonitrile on the first intermediate to allow the liquid succinonitrile to soak the first intermediate, cooling the liquid succinonitrile to solidify, and forming the second intermediate;

[0027] And / or, the temperature at which the succinonitrile is heated is 80-90°C.

[0028] According to an embodiment of the present application, after forming the second intermediate, the method further includes: immersing the second intermediate in the lithium salt solution, and drying to obtain a composite solid electrolyte.

[0029] According to an embodiment of the present application, the thickness of the composite solid electrolyte is 30-50 μm.

[0030] The present application also provides a composite solid electrolyte, which is prepared by the composite solid electrolyte preparation method described above.

[0031] The present application also provides a lithium solid-state battery, which includes the composite solid-state electrolyte described above.

[0032] Compared with the prior art, the beneficial effects of this application include:

[0033] The present application utilizes PVDF fiber support membrane as a support structure, which can not only significantly enhance the mechanical strength of the solid electrolyte film, but also the PVDF fiber support membrane can be used as an ion-conducting network to help transport lithium ions. Succinonitrile is used as an ion-conducting agent and is coated on the outside of the PVDF nanofiber. The composite film absorbs the lithium salt solution and forms a ternary eutectic system of PVDF-succinonitrile-lithium salt during the drying process. The composite solid electrolyte prepared by the method of the present application has a smaller thickness and higher conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0035] Figure 1 It is a flow chart of the preparation method of the composite solid electrolyte of the present application;

[0036] Figure 2 It is a structural comparison diagram of a composite solid electrolyte prepared using traditional PVDF powder and a composite solid electrolyte prepared using the method of the present application;

[0037] Figure 3 are SEM images of different stages in the preparation process of the composite solid electrolyte of the present application;

[0038] Figure 4 is an EDS-Mapping element analysis diagram of a random area on the side of the PSDL electrolyte membrane prepared in Example 1;

[0039] Figure 5 It is the XRD pattern of PSDL electrolyte film under different compositions and states;

[0040] Figure 6 It is the infrared spectra of different components and states in PSDL electrolyte film;

[0041] Figure 7 is the adsorption energy diagram of PVDF with DMF and SN respectively calculated by DFT;

[0042] Figure 8 is a thermogravimetric analysis graph of the PSDL prepared in Example 1;

[0043] Fig. 9 Comparative stress-strain curves of the PSDL electrolyte film prepared in Example 1, the PDL prepared in Comparative Example 1, and the PfDL prepared in Comparative Example 2;

[0044] Fig.10 The figure is a test result of using an atomic force microscope (AFM) to measure the upper surface roughness of the PSDL prepared in Example 1, the PfDL prepared in Comparative Example 2, and the PDL prepared in Comparative Example 1;

[0045] Fig.11 EIS electrochemical impedance curves of full cells and steel-on-steel cells composed of PSDL prepared in Example 1, PfDL prepared in Comparative Example 2, and PDL electrolyte prepared in Comparative Example 1 and NCM811 / Li metal;

[0046] Fig.12 EIS impedance spectra of the PSDL prepared in Example 1 at different temperatures;

[0047] Fig.13 Arrhenius curves of the PSDL prepared in Example 1, the PfDL prepared in Comparative Example 2, and the PDL prepared in Comparative Example 1;

[0048] Fig.14 Polarization curves and initial and stable impedance diagrams of Li / PSDL / Li symmetric cells;

[0049] Fig.15 LSV curves of the PSDL prepared in Example 1, the PfDL prepared in Comparative Example 2, and the PDL prepared in Comparative Example 1;

[0050] Fig.16 The calculation results of HOMO / LUMO energy levels of DMF, PVDF and SN are shown in the figure;

[0051] Fig.17 The Li / Li symmetric cells of the PSDL prepared in Example 1, the PfDL prepared in Comparative Example 2, and the PDL prepared in Comparative Example 1 were prepared at room temperature and 0.1 mA cm -2 The following cycle diagram;

[0052] Fig.18 A comparison chart of limiting current density of Li / Li symmetric cells of PSDL prepared in Example 1 and PDL prepared in Comparative Example 1;

[0053] Fig.19 The cycling diagram of the full battery using the PSDL prepared in Example 1, the PfDL prepared in Comparative Example 2, and the PDL prepared in Comparative Example 1 as electrolytes at room temperature and 0.1C rate;

[0054] Fig. 20 The cycling diagram of the full battery using the PSDL prepared in Example 1, the PfDL prepared in Comparative Example 2, and the PDL prepared in Comparative Example 1 as electrolytes at 1C rate at room temperature;

[0055] Fig.21 The cycling diagram of the full battery using the PSDL prepared in Example 1, the PfDL prepared in Comparative Example 2, and the PDL prepared in Comparative Example 1 as electrolytes at room temperature and 0.5C rate;

[0056] Fig. 22 The capacity-voltage curve of NCM811 / PSDL / Li battery at room temperature and 0.5C;

[0057] Fig.23 The charge-discharge cycle and capacity-voltage curve of NCM811 / PSDL / Li battery at room temperature and 0.5C rate in the voltage range of 2.8-4.5V;

[0058] Fig.24 The cycling diagram of the full battery with PSDL prepared in Example 1, PfDL prepared in Comparative Example 2 and PDL prepared in Comparative Example 1 as electrolyte at different rates at room temperature;

[0059] Fig.25 The capacity-voltage curves of NMCM811 / PSDL / Li batteries at different cycle rates;

[0060] Fig.26 This is the SEM image of the membrane surface after the SN coated PVDF fiber membrane adsorbed DMF / LiFSI and dried without adding LLZTO ceramic powder;

[0061] Fig. 27 is a comparison chart of XRD of PSDL5 prepared in Example 2, PSDL7.5 prepared in Example 1, and PSDL10 prepared in Example 3;

[0062] Fig.28 This is a comparison of the thickness of the electrolyte films prepared at different LiFSI concentrations;

[0063] Fig.29 The tensile strength test curves of PSDL5 prepared in Example 2, PSDL7.5 prepared in Example 1, and PSDL10 prepared in Example 3;

[0064] Fig.30 Thermogravimetric analysis curves of PSDL5, PSDL7.5 and PSDL10 without adding LLZTO ceramic powder;

[0065] Fig.31 Phase diagram analysis of the effect of LiFSI on the phase behavior of PVDF / SN binary system;

[0066] Fig.32 The infrared images of PSDL5 prepared in Example 2, PSDL7.5 prepared in Example 1, and PSDL10 prepared in Example 3;

[0067] Fig.33 EIS impedance curves of full cells and steel-on-steel cells using PSDL5 prepared in Example 2, PSDL7.5 prepared in Example 1, and PSDL10 prepared in Example 3 as electrolytes;

[0068] Fig.34 The cycling diagram of the full battery composed of PSDL5 prepared in Example 2, PSDL7.5 prepared in Example 1 and PSDL10 prepared in Example 3, NCM811 positive electrode and lithium metal negative electrode at room temperature and 1C condition;

[0069] Fig.35 The capacity-voltage curve of the NCM811 / PSDL7.5 / Li full battery assembled with the PSDL7.5 prepared in Example 1 as the electrolyte;

[0070] Fig.36 The cycling diagram of the full battery composed of PSDL5 prepared in Example 2, PSDL7.5 prepared in Example 1 and PSDL10 prepared in Example 3, NCM811 positive electrode and Li metal negative electrode at different rates at room temperature;

[0071] Fig.37 The lithium-lithium symmetric battery assembled from PSDL5 prepared in Example 2, PSDL7.5 prepared in Example 1, and PSDL10 prepared in Example 3 had a charge / discharge rate of 0.1 mA cm at room temperature.-2 Circulation diagram of

[0072] Fig.38 This is a comparison chart of the cycle performance of a full battery assembled with the PSDL prepared in Example 1 and the composite solid electrolyte prepared in Comparative Example 3 at room temperature and 0.1C rate. DETAILED DESCRIPTION

[0073] As used herein:

[0074] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0075] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0076] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0077] In these examples, parts and percentages are by mass unless otherwise indicated.

[0078] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.

[0079] “And / or” is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0080] A method for preparing a composite solid electrolyte, comprising:

[0081] Loading fast ion conductor ceramic particles on the PVDF fiber support membrane to form a first intermediate;

[0082] adsorbing succinonitrile onto the first intermediate to form a second intermediate;

[0083] The lithium salt solution is adsorbed onto the second intermediate and dried to obtain a composite solid electrolyte.

[0084] The PVDF fiber support membrane of the present application has high electrical conductivity and good supporting effect, which not only enables it to have good mechanical strength and electrochemical properties, but also can effectively reduce the thickness of the solid electrolyte, which is very necessary for the mass production of solid electrolytes, and provides a reliable solution for the research of high-energy-density and long-life solid-state lithium-ion batteries that can be mass-produced.

[0085] According to an embodiment of the present application, the fast ion conductor ceramic includes at least one of LLZTO, LLZO, LLTO, and LATP;

[0086] And / or, the lithium salt includes at least one of LiPF6, LiFSI, and LiTFSI.

[0087] According to an embodiment of the present application, the thickness of the PVDF fiber support membrane is 10 to 40 μm; for example, the thickness of the PVDF fiber support membrane can be 10 μm, 18 μm, 25 μm, 30 μm, 35 μm, 40 μm or any value between 10 and 40 μm.

[0088] Those skilled in the art can directly purchase a PVDF fiber support membrane with a thickness of 10 to 40 μm, or can prepare a PVDF fiber support membrane with a thickness of 10 to 40 μm by hot pressing a plurality of single-layer membranes through a hot pressing process.

[0089] And / or, the porosity of the PVDF fiber support membrane is 60% to 80%; for example, the porosity of the PVDF fiber support membrane can be 60%, 66%, 71%, 78%, 80% or any value between 60% and 80%.

[0090] And / or, the mass ratio of the fast ion conductor ceramic to the PVDF fiber support membrane is 1:5 to 1:8; for example, the mass ratio of the fast ion conductor ceramic to the PVDF fiber support membrane can be 1:5, 1:6, 1:7, 1:8 or any value between 1:(5~8).

[0091] And / or, the content ratio of the succinonitrile to the PVDF fiber support membrane is 1:(1400-1600) ml / mg; for example, the content ratio of the succinonitrile to the PVDF fiber support membrane can be 1:1400 ml / mg, 1:1500 ml / mg, 1:1600 ml / mg, or any value between 1:(1400-1600) ml / mg.

[0092] And / or, the lithium salt solution comprises a lithium salt and an amide solvent;

[0093] And / or, the concentration of the lithium salt solution is 5 to 10 g / L, preferably 7 to 8 g / L; for example, the concentration of the lithium salt solution can be 5 g / L, 5.5 g / L, 6 g / L, 6.5 g / L, 7 g / L, 7.5 g / L, 8 g / L, 8.5 g / L, 9 g / L, 9.5 g / L, 10 g / L or any value between 5 and 10 g / L.

[0094] And / or, the mass ratio of the lithium salt solution to the PVDF fiber support membrane is 7: (280-320) ml / mg; for example, the mass ratio of the lithium salt solution to the PVDF fiber support membrane can be 7: 280 ml / mg, 7: 290 ml / mg, 7: 300 ml / mg, 7: 310 ml / mg, 7: 320 ml / mg or any value between 7: (280-320) ml / mg.

[0095] And / or, the drying temperature is 50°C to 60°C, and the drying time is 12 to 15 hours. For example, the drying temperature can be 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C, 60°C or any value between 50°C and 60°C, and the drying time can be 12 hours, 13 hours, 14 hours, 15 hours or any value between 12 and 15 hours.

[0096] According to an embodiment of the present application, the PVDF fiber support membrane includes a PVDF electrospun fiber membrane;

[0097] The forming of the first intermediate comprises: dropping a fast ion conductor ceramic suspension onto the PVDF fiber support membrane, and drying to remove the solvent in the fast ion conductor ceramic suspension to obtain the first intermediate;

[0098] The fast ion conductor ceramic suspension includes fast ion conductor ceramic and alcohol solvent, and the content ratio of the fast ion conductor ceramic to the alcohol solvent is (1-2.5):1 mg / ml; for example, the content ratio of the fast ion conductor ceramic to the alcohol solvent can be 2.5:1 mg / ml, 1.7:1 mg / ml, 1.25:1 mg / ml, 1:1 mg / ml, or any value between (1-2.5):1 mg / ml.

[0099] and / or, the alcohol solvent comprises ethanol;

[0100] And / or, the amide solvent includes DMF.

[0101] According to an embodiment of the present application, forming the first intermediate includes: uniformly dripping a fast ion conductor ceramic suspension onto the PVDF fiber support membrane, then drying, turning over, and repeating the dripping, drying, and turning over operations until the fast ion conductor ceramic suspension is completely dripped. The fast ion conductor particles penetrate into the PVDF fiber support membrane as the solvent is dripped, achieving uniform mixing.

[0102] According to an embodiment of the present application, forming the second intermediate includes: heating succinonitrile at a temperature greater than or equal to the melting point of succinonitrile to obtain liquid succinonitrile, dripping the liquid succinonitrile on the first intermediate to allow the liquid succinonitrile to soak the first intermediate, cooling the liquid succinonitrile to solidify, and forming the second intermediate;

[0103] And / or, the temperature at which the succinonitrile is heated is 80-90° C. For example, the temperature at which the succinonitrile is heated can be 80° C., 83° C., 88° C., 90° C., or any value between 80 and 90° C.

[0104] According to an embodiment of the present application, after forming the second intermediate, the method further includes: immersing the second intermediate in the lithium salt solution, and drying to obtain a composite solid electrolyte.

[0105] According to an embodiment of the present application, the thickness of the composite solid electrolyte is 30-50 μm. For example, the thickness of the composite solid electrolyte can be 30 μm, 35 μm, 40 μm, 45 μm, 50 μm or any value between 30 and 50 μm.

[0106] The present application also provides a composite solid electrolyte, which is prepared by the composite solid electrolyte preparation method described above.

[0107] The present application also provides a lithium solid-state battery, which includes the composite solid-state electrolyte described above.

[0108] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0109] The information of the reagents used in the following examples and comparative examples is as follows:

[0110] The PVDF fiber support membrane is a PVDF electrospun fiber membrane with a thickness of 30 μm and a porosity of 60% to 80%;

[0111] LLZTO for Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 ;

[0112] PVDF powder is PVDF761([C2F2H2] n , Mw=300000).

[0113] 1. Preparation of composite solid electrolyte

[0114] Example 1

[0115] Embodiment 1 provides a composite solid electrolyte, and its preparation method comprises the following steps:

[0116] (1) Cut with a radius of 3 cm, the area is about 28.26 cm 2 , a PVDF electrospun fiber membrane with a mass of about 300 mg was used as a support.

[0117] (2) Weigh 50 mg of LLZTO nanoparticles and evenly disperse them in 20 ml of ethanol. Ultrasonicate for 20 minutes to make them evenly dispersed. Use a dropper to evenly drop the LLZTO ethanol suspension on the PVDF support fiber membrane, then put it in an oven to dry, turn it over and repeat this operation until all the suspension is dropped.

[0118] (3) Then, heat succinonitrile to 80°C to dissolve it, take 0.2 ml (about 4 drops) of succinonitrile solution and drop it onto the laminated film, and move the edge slightly and slowly to gradually wet the entire film, and wait until the temperature drops and the succinonitrile solidifies.

[0119] (4) Prepare a 7.5 g / L LiFSI DMF solution. Take 7 ml of lithium salt solution to a culture dish, immerse the prepared film in the solution, place it in a 55°C constant temperature oven to dry for 13 hours, and then take it out to obtain a composite solid electrolyte, namely PSDL or PSDL7.5 below. The thickness of the composite solid electrolyte in Example 1 is 40 μm. Cut it into discs of solid electrolyte film for standby use.

[0120] Example 2

[0121] The composite solid electrolyte was prepared by referring to the method of Example 1. The other steps were the same as those of Example 1, except that in step (4) of Example 2, a 5 g / L LiFSI DMF solution was used.

[0122] In Example 2, a composite solid electrolyte PSDL5 was obtained. The thickness of the composite solid electrolyte in Example 2 was 37 μm.

[0123] Example 3

[0124] The composite solid electrolyte was prepared by referring to the method of Example 1. The other steps were the same as those of Example 1, except that in step (4) of Example 3, a 10 g / L LiFSI DMF solution was used.

[0125] In Example 3, a composite solid electrolyte PSDL10 is obtained. The thickness of the composite solid electrolyte in Example 3 is 50 μm.

[0126] Comparative Example 1

[0127] 200g of PVDF powder, 40mg of LLZTO nanoparticles, and 15ml of DMF solution with a concentration of 9g / L LiFSI were mixed, and the solution was stirred for 3 hours to obtain a mixed slurry. The stirred solution was poured into a petri dish, placed in a 55°C constant temperature oven and dried for 23 hours, and then taken out to obtain a composite solid electrolyte PDL, which was cut into a disc solid electrolyte film for standby use. The thickness of the composite solid electrolyte in Comparative Example 1 was 120μm.

[0128] Comparative Example 2

[0129] The composite solid electrolyte was prepared by referring to the method of Example 1. The other steps were the same as those of Example 1, except that step (3) was omitted in Comparative Example 2, and the intermediate prepared in step (2) was directly subjected to step (4).

[0130] Comparative Example 2 obtained a composite solid electrolyte PfDL, and the thickness of the composite solid electrolyte in Comparative Example 2 was 40 μm.

[0131] Comparative Example 3

[0132] 200g of PVDF powder, 40mg of LLZTO nanoparticles, and 15ml of DMF solution with a concentration of 9g / L LiFSI were mixed, and the solution was stirred for 3 hours to obtain a mixed slurry. 0.2ml (about 4 drops) of 80°C succinonitrile liquid was added to the stirred solution and mixed evenly. The mixed solution was poured into a culture dish, placed in a 55°C constant temperature oven and dried for 23 hours, and then taken out to obtain a composite solid electrolyte, which was cut into a disc solid electrolyte film for standby use. The thickness of the composite solid electrolyte in Comparative Example 3 is 120μm.

[0133] 2. Basic Electrochemical Characterization

[0134] like Figure 1 As shown, LLZTO inorganic ceramic nanoparticles are uniformly dispersed in an ethanol solution in a suspension state, and are compounded with a PVDF nanofiber membrane by uniform dripping, with a small amount of uniform dripping each time to ensure that the ceramic powder is uniformly distributed in the horizontal direction. The ceramic powder nanoparticles adhere to the PVDF nanofibers as the ethanol penetrates, so that the ceramic powder can be uniformly distributed in the longitudinal direction. In addition, due to the addition of succinonitrile (SN), the ion conductivity of the electrolyte membrane is effectively improved. SN infiltrates the composite nanofiber membrane in a liquid state. When the temperature drops to room temperature, SN is wrapped in a solid form on the outside of the PVDF nanofiber and the LLZTO ceramic powder, and the white composite fiber membrane is translucent. After that, the fiber membrane is immersed in a DMF solution of LiFSI and dried in an oven. The prepared composite solid electrolyte is milky white. Due to the addition of lithium salt and SN, the proportion of the amorphous region of the polymer is increased, the spacing between the PVDF molecular chains is widened, the PVDF nanofibers swell, the crystallinity is reduced, and the ionic conductivity is improved. At the same time, this also increases the thickness of the electrolyte film, and the mechanical strength is reduced compared to the original PVDF nanofiber. From the internal microstructure, PVDF nanofibers expand and mix with SN to form a eutectic solid solution, and will wrap some LLZTO nanoparticles therein, thus forming an ordered and continuous lithium ion transmission network. Compared with traditional composite solid electrolytes, lithium ions are difficult to be transmitted continuously between ceramics and polymers. The ordered and coherent structure of this application makes ion transmission more efficient.

[0135] Figure 2 On the left is a schematic diagram of the structure of a composite solid electrolyte prepared using traditional PVDF powder. Figure 2 The right side is a schematic diagram of the structure of the composite solid electrolyte prepared by the method of the present application. Figure 2 As can be seen from the left figure, the LLZTO in the composite solid electrolyte prepared using traditional PVDF powder cannot be evenly distributed in the vertical direction. This is because the LLZTO ceramic powder will settle to the bottom of the solution due to gravity during the drying of the liquid in the culture dish. The method of this application can avoid this problem. Figure 2As can be seen from the right figure, the ceramic powder in the composite solid electrolyte of the present application is evenly distributed in the longitudinal direction. This is because the ceramic powder nanoparticles are attached to the PVDF nanofibers as the ethanol penetrates, avoiding the problem of settling to the bottom of the solution due to gravity.

[0136] Figure 3 are SEM images of different stages in the preparation process of the composite solid electrolyte of this application, Figure 3 (a) and 3(b) are SEM images of the surface of PVDF fiber membrane. Figure 3 (c) and 3(d) are SEM images of the surface of PVDF fiber membrane after PVDF fiber membrane is composited with LLZTO ceramic powder. Figure 3 (e) and 3(f) are SEM images of LLZTO composite PVDF fiber membranes after being impregnated with succinonitrile. Figure 3 (g) and 3(h) are SEM images of the PSDL electrolyte film surface. Figure 3 (i) and 3(j) are SEM images of the side of the PSDL electrolyte film. Figure 3 (a) and 3(b) show that the PVDF fiber membrane is composed of multiple single nanofibers, most of which have a diameter of about 200-400nm. The porosity of the fiber membrane is about 70%. Its loose and porous structure allows the nano-LLZTO ceramic particles to penetrate into the fiber membrane through ethanol. Figure 3 (c) and 3(d) show that, whether on the outer surface or the shallow inner surface, nano-scale LLZTO ceramic particles are attached to the PVDF fiber and penetrate into the interior through the pores. The lateral distribution is relatively uniform, and there is no large-scale particle agglomeration. Figure 3 (e) and 3(f), it can be seen that after being infiltrated with succinonitrile, the microstructure of the LLZTO composite PVDF fiber membrane did not change significantly, but the macroscopic color changed from pure white to translucent. Figure 3 (g) and 3(h) are SEM images of the LLZTO composite ternary eutectic system (PVDF / SN / LiFSI) solid electrolyte film (PSDL) after being immersed in 7.5g / L LiFSI / DMF solution and dried. During the drying process, PVDF, SN and LiFSI form a low-crystallinity ternary eutectic system with strong ion conductivity. DMF is used as a solvent, and the infiltration of LiFSI and the volatilization of DMF finally form the ternary eutectic system. Figure 3It can be seen from (g) and 3(h) that during the recrystallization process, the PVDF fiber expands and becomes more fluffy. This is because the presence of SN, lithium salt and ceramic powder increases the molecular distance of PVDF and the amorphous area. In addition, since SN is coated on the outside of the PVDF fiber and LLZTO particles, most of the LLZTO particles after recrystallization are wrapped inside the eutectic. The surface of the film after recrystallization presents a loose porous structure. Figure 3 (i) and 3(j) are SEM images of the side of the PSDL electrolyte film. Figure 3 (i) and 3(j) show that the thickness of the PSDL electrolyte film is 40 μm, and the internal fiber structure and the incorporated ceramic powder particles can be clearly seen from the side.

[0137] Figure 4 This is the EDS-Mapping element analysis diagram of the random area on the side of the PSDL electrolyte film. Figure 4 It can be seen that the C and F elements representing PVDF and the N element representing SN are evenly distributed without obvious interfaces.

[0138] Figure 5 is the XRD diagram of the PSDL electrolyte film under different components and states. PVDF+LLZTO+SN+DMF / LiFSI represents the PSDL prepared in Example 1. The XRD diffraction peaks of LLZTO and PVDF fiber membrane monomers are very obvious. After the two are compounded, the diffraction peak of the composite fiber membrane is the superposition of the diffraction peaks of two separate materials. After adding succinonitrile, the peak signal of SN is obvious, and the diffraction peak of the PSDL formed after recrystallization is the superposition of several substances. The peak intensity of SN becomes very weak. This is because in the new eutectic system, SN does not exist in a single form, and the components are still mainly PVDF and LLZTO. It’s just that the peak intensity is significantly reduced due to the formation strength of the eutectic system, indicating that the crystallinity of the electrolyte film is low and the amorphous region accounts for a relatively large proportion.

[0139] Figure 6 is the infrared spectra of different components and states in the PSDL electrolyte film. PVDF+SN+DMF / LiFSI+LLZTO represents the PSDL prepared in Example 1. Figure 6 It can be seen that after adding SN, at 2250cm -1 The vibration of the nitrile functional group of -C≡N can be clearly seen at the position of 1700cm-1. After the addition of DMF / LiFSI to form a eutectic system, the vibration of the nitrile functional group is significantly weakened, and the -1 The enhanced vibration of the C=O carbon-oxygen double bond at the position indicates that there is incompletely dried DMF adsorbed by PVDF in the system, which once again shows that the content of SN in the system is low and exists in a non-independent form.

[0140] Figure 7 is the adsorption energy diagram of PVDF with DMF and SN calculated by DFT, Figure 7 It can be seen that the adsorption energy of PVDF and DMF is -0.28eV, while the adsorption energy of PVDF and SN is -0.4eV, which means that SN is more easily adsorbed by PVDF. Therefore, in the process of infiltrating DMF / LiFSI solution, SN is not dissolved in DMF, but first combines with PVDF. PVDF first adsorbs SN, then DMF and LiFSI, and then forms a ternary eutectic system with the volatilization of DMF. Due to the adsorption of PVDF, a small amount of non-volatile DMF is preserved in the eutectic system to reduce the crystallinity and promote ion transport.

[0141] Figure 8 The thermogravimetric analysis diagram of PSDL, where the black curve is the heating weight loss data of the sample, and the red curve is the endothermic curve. Figure 8 It can be seen that LiFSI and LLZTO account for about 20% of the total weight in PSDL (LLZTO is added at a mass ratio of 10-15% during the preparation process).

[0142] Fig. 9 PVDF+LLZTO+DMF / LiFSI represents the PDL prepared in Comparative Example 1, and PVDF Film+LLZTO+DMF / LiFSI represents the PfDL prepared in Comparative Example 2. Fig. 9 It can be seen that compared with the PDL prepared by PVDF powder, the yield stress of the composite solid electrolyte membrane after the introduction of the support is greatly improved. After adding SN, the yield stress of the film decreases, but the strain increases, indicating that the addition of SN slightly deteriorates the mechanical properties of the membrane, but slightly enhances the toughness, because the addition of SN increases the proportion of amorphous areas in the electrolyte membrane.

[0143] Fig.10 The test results of the upper surface roughness of PSDL, PfDL and PDL using atomic force microscopy (AFM) are shown in Figure 1. Fig.10 It can be seen that the surface roughness of PSDL is the lowest, PDL is similar to PSDL, and PfDL has the highest surface roughness. Due to the coating and recrystallization process of SN, the ceramic powder particles that have not penetrated the upper surface of PSDL will be coated inside by the eutectic rather than exposed on the surface. The formation of the eutectic system can play a role in surface homogenization, so the roughness is relatively low.

[0144] 3. Electrochemical performance test

[0145] Preparation of positive electrode: 160mg NCM811 powder, 20mg Super P, 20mg binder PVDF. The above raw materials are fully mixed and ground evenly, then added into DMF solution and stirred into slurry, and then coated on aluminum foil. The active material loading is about 2mg / cm 2 , and the positive electrode sheet is obtained after slicing.

[0146] Battery assembly: The assembly of the whole battery, the positive electrode material is the prepared NCM811 positive electrode, the negative electrode material is the metal Li sheet, and the button battery assembly process is followed, and the negative electrode shell, gasket, steel sheet, lithium sheet, solid electrolyte, positive electrode sheet, steel sheet, and positive electrode shell are assembled in this order. Then the battery is compressed and sealed for testing.

[0147] The Li symmetric battery replaces the positive electrode sheet with a lithium sheet, and the other processes are the same.

[0148] The assembly of the steel symmetrical battery directly sandwiches the solid electrolyte between the positive and negative steel sheets, and the other processes are the same. All battery assemblies are completed in an Ar-filled glove box, where the water and oxygen partial pressures are H2O < 0.5 ppm and O2 < 0.5 ppm, respectively.

[0149] Fig.11 EIS electrochemical impedance curves of full cells and steel-on-steel cells composed of PSDL, PfDL and PDL electrolytes and NCM811 / Li metal. Fig.11 It can be seen that the EIS impedances of the full batteries composed of the three electrolytes PSDL, PfDL and PDL at room temperature are 60Ω, 174Ω and 175Ω respectively, while the impedances of the steel-to-steel batteries at room temperature are 4Ω, 17.5Ω and 18Ω respectively. Their thicknesses are 40μm, 40μm and 120μm respectively. The area of ​​the electrolyte film used for button cell assembly is 1.13cm 2 According to the formula σ=L / R*S, the ionic conductivity of the three electrolytes at room temperature can be calculated to be 0.89*10 -3 , 0.20*10 -3 and 0.59*10 -3 S cm -1 It can be seen that the addition of SN has a very significant effect on improving ionic conductivity.

[0150] Fig.12 The EIS impedance spectra of PSDL at different temperatures show that the impedance of PSDL steel-to-steel battery changes significantly with temperature, but the difference is not large. The impedance is about 6Ω at 10℃, and only 2Ω at 70℃. The corresponding ionic conductivities are 0.59*10 -3 S cm -1 and 1.77*10 -3 S cm -1 .

[0151] Fig.13 The Arrhenius curves of the three electrolytes PSDL, PfDL and PDL are shown in Figure 1. According to the Arrhenius equation σ = σ0exp (-Ea / RT), the activation energies of the three electrolytes PSDL, PfDL and PDL are calculated to be 0.18 eV, 0.24 eV and 0.25 eV, respectively. It can be seen that although the PVDF nanofiber support structure can provide a continuous ion conduction path, it does not significantly help improve the ion conductivity without improving the overall ion conductivity. After adding SN, the ion conductivity is significantly improved.

[0152] Fig.14 The polarization curve and initial and stable impedance diagram of Li / PSDL / Li symmetric battery are shown in the formula The calculated lithium ion transfer number of PSDL is 0.244.

[0153] Fig.15 is the LSV curve of PSDL, PfDL and PDL, Fig.15 It can be seen that the oxidation potentials of PfDL and PDL are about 4.5V, while the oxidation potential of PSDL is significantly increased to about 4.8V.

[0154] Fig.16 The HOMO / LUMO energy level calculation results of DMF, PVDF and SN are shown in Figure 2. Fig.16 It can be seen that SN has a lower HOMO energy level and stronger antioxidant property, so its addition can effectively help improve the oxidation potential of the electrolyte, which also explains why the oxidation potential of PSDL is significantly higher than that of PfDL and PDL.

[0155] Fig.17 The Li / Li symmetric cells of PSDL, PfDL and PDL at room temperature and 0.1 mA cm -2 The cycling diagram shows the cycling conditions under the following conditions, where the PDL and PfDL batteries short-circuited after about 140 hours and 380 hours of cycling, respectively, while the PSDL can be stably cycled for more than 2000 hours. Its early stable cycling polarization potential was about 25mV, and the polarization potential was only 30mV after 1000 hours of cycling. After 2000 hours of cycling, the polarization potential was about 40mV.

[0156] Fig.18 Comparison of the limiting current density of PSDL and PDL Li / Li symmetric cells. The limiting current density of Li / PDL / Li is only 0.9 mA cm -2 , and the limiting current density of Li / PSDL / Li can reach 1.9 mA cm -2This shows that the excellent ion conductivity of PSDL improves the transmission efficiency of lithium ions and the stability of the interface with lithium metal, making less Li + The retained electrolyte gaps reduce the possibility of damage to the electrolyte film. At the same time, the ion deposition on the lithium metal surface is also improved accordingly, which reduces the growth rate of lithium dendrites and dead lithium at the interface, thereby achieving stable battery cycling.

[0157] In order to more systematically evaluate the electrochemical performance of the electrolyte prepared in the present application, the inventors assembled full batteries using PSDL, PfDL and PDL as electrolytes, respectively, and tested the long cycles of these batteries at different rates.

[0158] Fig.19 The cycling diagram of the full battery with PSDL, PfDL and PDL as electrolytes at room temperature and 0.1C rate. The first discharge capacity of the NCM811 / PSDL / Li battery is 188 mAh g -1 The coulombic efficiency was 77.1% in the first week and then stabilized at about 180 mAh g -1 After 100 cycles, the capacity can be maintained at 163 mAh g -1 This is because the introduction of SN into PSDL significantly improves the ion conductivity, so the discharge capacity of the whole battery is the highest. Although the ion conductivity of PfDL is not as good as that of PSDL, the introduction of PVDF support structure has significantly improved the cycle stability.

[0159] Fig. 20 Figure 2 shows the cycling performance of full batteries with PSDL, PfDL and PDL as electrolytes at 1C rate at room temperature. The first discharge capacity of NCM811 / PSDL / Li battery at 1C rate can reach 184 mAh g -1 , and then stabilized at 162mAh g -1 After 1000 stable cycles, the capacity is 97 mAh g -1 , the capacity retention rate is 62.5%. This shows that due to the support structure and the addition of SN, the ion conductivity of PSDL is not only improved, but also its long-cycle stability at high rates is significantly improved.

[0160] Fig.21 The cycling diagram of the full battery with PSDL, PfDL and PDL as electrolyte at 0.5C rate at room temperature; Fig. 22 The capacity-voltage curve of NCM811 / PSDL / Li battery at room temperature and 0.5C. Fig.21 and Fig. 22 It can be seen that the first discharge capacity of NCM811 / PSDL / Li battery at 0.5C rate is 173mAh g -1, and then stabilized at 168mAh g -1 The capacity retention rate is high in the first 100 weeks, and the charge and discharge platform is obvious. After 300 weeks of stable cycling, the capacity is 130 mAh g -1 The capacity retention rate is 77.18%. In comparison, the full batteries of PfDL and PDL have relatively low capacities, and the cycle stability of NCM811 / PDL / Li battery is poor, with overcharging occurring after 100 cycles.

[0161] Fig.23 The charge-discharge cycle and capacity-voltage curve of NCM811 / PSDL / Li battery at room temperature and 0.5C rate in the voltage range of 2.8-4.5V. The addition of SN effectively improves the oxidation potential of PSDL and the voltage is increased to 4.5V, so the specific capacity of the battery is also improved accordingly, and the first discharge capacity can reach 191mAh g -1 After 100 cycles of stable cycling, the capacity is still maintained at 166 mAh g -1 From the capacity-voltage curve, we can see that the voltage platform is obvious. Although there is no obvious charge and discharge platform above 4.3V, there is still capacity contribution.

[0162] Fig.24 The cycling diagram of full batteries with PSDL, PfDL and PDL as electrolytes at different rates at room temperature is shown below. Fig.25 The capacity-voltage curves of NMCM811 / PSDL / Li batteries at different cycle rates. Fig.24 and Fig.25 It can be seen that PSDL has excellent rate performance. The rate discharge step of NCM811 / PSDL / Li battery is obvious and the recovery is good. It can still provide 133mAh g at a rate of 5C. -1 The specific capacity of the battery was 182 mAh g after the battery was restored to 0.1C. -1 , which is almost the same as the 0.1C rate capacity at the beginning of the cycle. In comparison, PfDL and PDL are far inferior to PSDL in terms of specific capacity at high rates and capacity stability at different rates.

[0163] The ternary eutectic system is formed by adsorption and recrystallization of PVDF, SN and LiFSI during the DMF drying process. The inventors found through the performance test results of the electrolytes prepared in Examples 1-3 that as the content of LiFSI in the electrolyte film increases, the electrolyte film gradually tends to a liquid phase, and the mechanical strength of the film decreases significantly.

[0164] Fig.26This is the SEM image of the surface of the PVDF / SN / LiFSI film without LLZTO added. It can be clearly seen from the figure that after the addition of SN and LiFSI and the infiltration and drying of DMF, the uniform and slender strip structure of the original PVDF electrospun fiber disappears due to the recrystallization process. The recrystallization causes the fiber to swell and become branched. However, the recrystallization process does not destroy the support structure, and the fiber membrane has an enhancing effect on the overall performance.

[0165] Fig. 27 This is the XRD comparison diagram of PSDL5, PSDL7.5 and PSDL10. Fig. 27 It can be seen that with the increase of LiFSI content, the XRD peak intensity weakens, especially for the PSDL10 sample, the LLZTO peak intensity is no longer obvious. This shows that with the increase of lithium salt content, the degree of LLZTO encapsulation also increases accordingly, the degree of homogenization increases, the crystallinity decreases, and the degree of amorphousness increases.

[0166] Fig.28 This is a comparison chart of the thickness of the electrolyte films prepared under different LiFSI concentrations. The thickness of the original PVDF electrospun fiber membrane is 30μm. The thickness of the PSDL membrane treated with DMF without LiFSI is slightly increased to about 34μm. The thicknesses of PSDL5, PSDL7.5 and PSDL10 with different LiFSI concentrations are 37μm, 40μm and 50μm, respectively. It can be seen that the amount of lithium salt added will affect the degree of expansion during the recrystallization process. The more lithium salt content, the greater the degree of expansion, the larger the PVDF molecular distance, the lower the plasticity, and the higher the proportion of amorphous region.

[0167] Fig.29 The tensile strength test curves of PSDL5, PSDL7.5 and PSDL10 films are shown in Figure 2. Fig.29 It can be seen that the maximum tensile strength of PSDL5 can reach 2.2MPa, while the tensile yield strength of PSDL10 is only about 0.8MPa, which shows that the increase of lithium salt content will reduce the plasticity of the material, increase the amorphous zone and sacrifice the mechanical strength.

[0168] Fig.30 Thermogravimetric analysis curves of PSDL5, PSDL7.5 and PSDL10 are shown in Table 1. Fig.30It can be seen that before 50℃, it is water weight loss, and the three materials have the same water absorption capacity in the air. 50-160℃ is DMF weight loss, and the DMF content in the three materials is basically the same, which shows that the increase in lithium salt content does not affect the system's adsorption capacity for DMF. Under the same drying temperature and time, the DMF content in the three samples is consistent. 160-320℃ is SN weight loss and 320-530℃ is PVDF weight loss, and the remaining components are mainly LiFSI. The weight loss curves of PSDL5 and PSDL7.5 from 160-530°C are similar, while the weight loss trajectory of PSDL10 in the range of 160-530°C is quite different from that of PSDL5 and PSDL7.5. The content ratios of SN and PVDF in the three samples are basically the same, and the only difference is the content of lithium salt. The inventors speculate that the reason for this difference is that the increase in lithium salt content increases the liquid phase ratio of the entire ternary eutectic system. When the lithium salt content reaches a certain critical value, the eutectic system transforms from the original phase to a solid-liquid mixed phase with a relatively higher liquid component ratio. This also corresponds to the test results of reduced crystallinity, increased amorphous region, reduced mechanical strength, and increased ion conductivity in the previous data. There are differences in certain physical and chemical properties between the new phase in PSDL10 and the phases in PSDL5 and PSDL7.5, which is reflected in the thermal weight loss, showing a completely different weight loss trajectory.

[0169] Fig.31The phase diagram analysis of the effect of LiFSI on the phase behavior of the PVDF / SN binary system is shown in Figure 1. If the binary phase diagram is used to represent the relationship between PVDF and SN in the system, it should be shown as the blue line when the LiFSI content is not increased, and the trend after increasing the amount of LiFSI added is shown by the red line. PVDF is a semi-crystalline polymer with five different crystal forms (α, β, γ, δ, ε), the more common of which are α, β, and γ phases. The molecular dipoles of the α phase (TGTG) are arranged in reverse order, so it is non-polar. The β phase (TTT) has an all-trans molecular structure and is the most polar, while the γ phase (T3G+T3G-) is between α and β. It can be seen that the molecular arrangement of the α phase is more orderly and the ion conductivity is relatively low, while the ion conductivity of the β or γ phase is stronger than that of the α phase. However, the molecular potential energy of the α phase is the lowest and it is a thermodynamically stable phase, so the α phase is generally obtained under crystallization conditions. Combined with the above experimental data, the inventor speculates that in the PVDF / SN binary system without considering LiFSI, the eutectic composition at room temperature is SN solid and a large amount of α phase and a small amount of β phase PVDF mixed phase, and when the composition ratio of SN increases and the PVDF composition ratio decreases, because SN increases the disorder of the system, the α phase ratio of the PVDF component in the mixed phase decreases and the β phase ratio increases, the polarity of the system increases, and the ion conductivity is enhanced. However, with the increase of lithium salt content, the system shows the same trend. Therefore, it is speculated that the increase of lithium salt is equivalent to moving the point of the system in the phase diagram (green five-pointed star) to the left, that is, moving the solid-liquid euphase line on the right to the right. While the β phase ratio in the system increases, the liquid phase component of the system also increases relatively, and the amorphous form and ion conductivity also increase accordingly. This has also been proven in infrared tests.

[0170] Fig.32 Infrared images of PSDL5, PSDL7.5 and PSDL10. Fig.32 It can be seen that the addition of DMF increases the -1 and 1000cm -1 The -C≡N vibration intensity of the nitrile functional group of LiFSI decreases, while after the addition of LiFSI, the -C≡N vibration intensity tends to be less obvious as its content increases, which is due to the formation of a homogenized eutectic system. -1The orange peak is caused by the C=O vibration of the carbon-oxygen double bond in DMF. Whether it is the sample dried in the DMF solution without LiFSI, or the PSDL5, PSDL7.5 and PSDL10 samples, the C=O vibration can be detected, indicating that the dried film still contains DMF. As the LiFSI content increases, although the DMF content does not increase, the C=O vibration degree increases. This is because as the LiFSI content increases, the liquid state of the system increases. At this time, DMF is more inclined to the free state in the system, and its functional groups are more easily detected, so the C=O vibration intensity increases. The peak at 1100cm -1 The enhancement of the sulfur-oxygen double bond O=S=O signal in the green region proves the increase of LiFSI content in the system. As we mentioned before, PVDF has multiple phases, which can be characterized in infrared, at 763cm -1 The vibration at 839cm is the vibration of α-phase PVDF, while the -1 The vibration of is considered to be the overlap of β-phase and γ-phase vibration. The inventors focus on the 600-900cm -1 This interval, 763cm -1 and 610cm -1 The vibration of is a sharp peak in pure PVDF sample. As the content of LiFSI increases, the sharp peak becomes less obvious and is replaced by a gentle curve. This proves that as the content of lithium salt increases, the proportion of α-phase PVDF decreases and the degree of molecular polarization increases. The corresponding peak at 839cm -1 and 675cm -1 The vibration of β-phase PVDF becomes more obvious with the increase of LiFSI content, which means that the proportion of β-phase PVDF increases with the increase of lithium salt content, which also verifies the inference of phase transformation and phase composition during recrystallization. That is, with the increase of LiFSI content, the crystalline phase will change, the proportion of β-phase in PVDF component will increase, the proportion of α-phase will decrease, the polarity of PVDF will increase, the plasticity of the system will decrease, the mechanical strength will decrease, and the ion conductivity will increase. The intuitive manifestation of this series of changes in electrochemical performance is EIS impedance.

[0171] Fig.33 The EIS impedance curves of full cells and steel-on-steel cells with PSDL5, PSDL7.5 and PSDL10 as electrolytes. From the data, it can be seen that whether it is a full cell or a steel-on-steel battery, the impedance of PSDL10 is the smallest, the impedance of PSDL7.5 is slightly larger than that of PSDL10, and the impedance of PSDL5 is the largest, which shows that the increase in lithium salt content can increase the ionic conductivity of the electrolyte.

[0172] In order to more comprehensively evaluate the electrochemical performance of electrolytes with different LiFSI contents, the inventors conducted performance tests of long cycles, rate cycles, and lithium-lithium symmetric batteries.

[0173] Fig.34 The figure shows the cycle status of full batteries composed of PSDL5, PSDL7.5 and PSDL10 with NCM811 positive electrode and lithium metal negative electrode at room temperature and 1C conditions. It can be seen that the capacity of the PSDL10 full battery is the highest at the beginning of the cycle, but its stability is very poor. It is overcharged after about 60 weeks and short-circuited after about 100 weeks. The capacity of the PSDL5 full battery is low and unstable. It also short-circuited after about 600 weeks, while the PSDL7.5 can be stably cycled for 1000 weeks.

[0174] Fig.35 The capacity-voltage curve of the NCM811 / PSDL7.5 / Li full battery assembled with PSDL7.5 as the electrolyte shows that its voltage platform is obvious and the charge and discharge capacity is relatively stable.

[0175] Fig.36 The figure shows the cycling conditions of full batteries composed of PSDL5, PSDL7.5 and PSDL10 with NCM811 positive electrode and Li metal negative electrode at different rates at room temperature. Since PSDL10 has a higher ionic conductivity, its electrochemical performance is basically consistent with PSDL7.5 under low cycle conditions. PSDL5 has a relatively low battery capacity due to its large impedance, but it can still be cycled at a high rate of 5C, and the capacity recovery after high-rate cycling is also relatively ideal.

[0176] Fig.37 The Li-Li symmetric cells assembled for PSDL5, PSDL7.5 and PSDL10 are 0.1 mA cm at room temperature. -2 The cycling diagram shows that PSDL10 has poor cycling stability due to its poor mechanical strength and short circuits after 270 hours.

[0177] In summary, as the concentration of LiFSI increases, a phase transition occurs during the recrystallization process, the polarity of the PVDF molecule increases, the plasticity of the system decreases, the mechanical strength decreases, and the ion conductivity increases. However, this does not mean that the comprehensive performance of the electrolyte is improved. On the contrary, due to the decrease in mechanical strength, the long-cycle stability of the electrolyte is greatly reduced. Therefore, the content of LiFSI is maintained at an equilibrium value to obtain the best electrochemical performance. Compared with Examples 2-3, Example 1 has better electrochemical performance. The ion conductivity of the composite solid electrolyte PSDL7.5 prepared in Example 1 can reach 0.89*10 -3 Scm -1The composite solid electrolyte PSDL7.5 was combined with the NCM811 positive electrode and the lithium metal negative electrode to assemble a full battery. The stable initial capacity can reach 188 mAh g at room temperature and 0.1C cycle. -1 The stable initial capacity of 1C cycle can reach 162mAh g -1 After 1000 cycles, the capacity retention rate can be maintained at 62.5%, and the full battery can still maintain 133mAh g at 5C rate. -1 In addition, succinonitrile increases the oxidation potential, and the battery can be charged to 4.5V and cycled stably at 0.5C for 100 weeks, with a stable initial capacity of about 191mAh g -1 That is, the concentration of the lithium salt solution is preferably 7.5 g / L.

[0178] Fig.38 The cycling diagram of the full battery assembled with the PSDL prepared in Example 1 and the composite solid electrolyte prepared in Comparative Example 3 at room temperature and 0.1C rate is shown in FIG. Fig.38 It can be seen that the cycle performance of the PSDL prepared in Example 1 is better than that of the composite solid electrolyte prepared in Comparative Example 3.

[0179] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

[0180] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. A method for preparing a composite solid electrolyte, characterized in that: include: Loading fast ion conductor ceramic particles on the PVDF fiber support membrane to form a first intermediate; adsorbing succinonitrile onto the first intermediate to form a second intermediate; The lithium salt solution is adsorbed onto the second intermediate and dried to obtain a composite solid electrolyte.

2. The method for preparing a composite solid electrolyte according to claim 1, characterized in that: The fast ion conductor ceramic includes at least one of LLZTO, LLZO, LLTO, and LATP; And / or, the lithium salt includes at least one of LiPF6, LiFSI, and LiTFSI.

3. The method for preparing a composite solid electrolyte according to claim 1, characterized in that: The thickness of the PVDF fiber support membrane is 10 to 40 μm; And / or, the porosity of the PVDF fiber support membrane is 60-80%; And / or, the mass ratio of the fast ion conductor ceramic to the mass ratio of the PVDF fiber support membrane is 1:5 to 1:8; and / or, the content ratio of the succinonitrile to the PVDF fiber support membrane is 1: (1400-1600) ml / mg; And / or, the lithium salt solution comprises a lithium salt and an amide solvent; And / or, the concentration of the lithium salt solution is 5 to 10 g / L; and / or, the mass ratio of the lithium salt solution to the PVDF fiber support membrane is 7: (280-320) ml / mg; And / or, the drying temperature is 50-60° C., and the drying time is 12-15 hours.

4. The method for preparing a composite solid electrolyte according to claim 3, characterized in that: The forming of the first intermediate comprises: dropping a fast ion conductor ceramic suspension onto the PVDF fiber support membrane, and drying to remove the solvent in the fast ion conductor ceramic suspension to obtain the first intermediate; The fast ion conductor ceramic suspension comprises fast ion conductor ceramic and alcohol solvent, and the content ratio of the fast ion conductor ceramic to the alcohol solvent is (1-2.5): 1 mg / ml; and / or, the alcohol solvent comprises ethanol; And / or, the amide solvent includes DMF.

5. The method for preparing a composite solid electrolyte according to claim 4, characterized in that: The forming of the first intermediate comprises: uniformly dripping the fast ion conductor ceramic suspension onto the PVDF fiber support membrane, followed by drying, turning over, and repeating the dripping, drying, and turning over operations until the fast ion conductor ceramic suspension is completely dripped.

6. The method for preparing a composite solid electrolyte according to claim 1, characterized in that: The forming of the second intermediate comprises: heating succinonitrile at a temperature greater than or equal to the melting point of succinonitrile to obtain liquid succinonitrile, dropping the liquid succinonitrile on the first intermediate to allow the liquid succinonitrile to soak the first intermediate, and cooling the liquid succinonitrile to solidify to form the second intermediate; And / or, the temperature at which the succinonitrile is heated is 80-90°C.

7. The method for preparing a composite solid electrolyte according to claim 1, characterized in that: After forming the second intermediate, the method further comprises: immersing the second intermediate in the lithium salt solution and drying to obtain a composite solid electrolyte.

8. The method for preparing a composite solid electrolyte according to any one of claims 1 to 7, characterized in that: The thickness of the composite solid electrolyte is 30-50 μm.

9. A composite solid electrolyte, characterized in that: The composite solid electrolyte is prepared by the method for preparing a composite solid electrolyte according to any one of claims 1 to 8.

10. A lithium solid-state battery, characterized in that: The lithium solid-state battery comprises the composite solid-state electrolyte according to claim 9.